Trend Analysis Of Financial Performance Of The Province Of Bali 2016 – 2020 - Ida I Dewa Ayu Yayati Wilyadewi; Ida Ayu Made Sasmita Dewi (Institute of Computer Science (IOCS), 2022)
It is important to measure financial performance for the entire organization, including the government, especially the Bali Provincial Government. Evaluation of the government's financial performance can be done by analyzing the financial statements. Based on these reviews, this study aims to analyze trends in the financial performance of the Bali Provincial government from 2016 - 2020. This research is a descriptive quantitative study with data collection techniques using literature studies. This study resulted that the financial performance of the Bali Provincial Government in terms of 2 (two) ratios, namely the independence ratio and the efficiency ratio. The evaluation of the financial assessment of the independence ratio shows that the ability of the Government of Bali to finance its own development, development and services to the community is moderate. Then the evaluation of the Bali Provincial Government's financial performance in terms of efficiency ratios for 5 years is inefficient which shows that the Bali Provincial Government's financial realization has not been able to manage the budget. Based on this calculation, the overall financial performance of the Bali Provincial Government cannot be said to be good considering that there are still indicators that do not meet the good category. This research is expected to be a recommendation material in the preparation of government policies, especially the Bali provincial government in carrying out development and services to.